Green Regenerative Hydrogel Wound Dressing Functionalized by Natural Drug‐Food Homologous Small Molecule Self‐Assembled Nanospheres. (5th November 2021) - Sun, Xinyu; Jia, Pei; Zhang, Hui; Dong, Mengna; Wang, Jiao; Li, Lihua; Bu, Tong; Wang, Xin; Wang, Li; Lu, Qingyou; Wang, Jihao
Abstract: The goal of regenerative wound healing dressings is to restore tissue function back to normal physiological activity and accelerate skin tissue regeneration at wound sites. The optimal strategy to achieve this purpose requires a balance between material functionality, degradation, safety, and tissue regrowth. Herein, for the first time, an ultrasonic‐triggered irreversible tending to equilibrium self‐assembly and ionic cross‐linking codriven strategy is proposed for producing multifunctional cinnamaldehyde‐tannic acid‐zinc acetate nanospheres (CA‐TA‐ZA NSs), realizing the fusion of hydrophilic and hydrophobic drug‐food small molecules. Moreover, a novel "all‐in‐one" chitosan (CS)‐based hydrogel functionalized by introducing drug‐food small molecules self‐assembled CA‐TA‐ZA NSs to the 3D network structures of CS is designed, integrating excellent antibacterial, antioxidant, anti‐inflammatory and reducing oxidative stress damage abilities. Additionally, the multifunctional CS‐based hydrogel can realize rapid in situ gelation at wound sites and completely cover the irregular wounds. All of these superiorities enable the CS‐based hydrogel to clean the wound microenvironment, induce skin tissue remodeling, promote blood vessel repair and hair follicle regeneration, restore the immune system back to normal physiological activity, and accelerate wound healing. Therefore, this study offers a new perspective for the design of advanced functional materials with great application potential in the biomedical field. Abstract : Inspired by the drug‐food homologous ingredients in cinnamon and red wine, an "all‐in‐one" chitosan‐based hydrogel modified by cinnamaldehyde and tannic acid, integrating antibacterial, antioxidant and anti‐inflammatory functions, is designed. The hydrogel can realize in situ gelation on wound sites, completely cover irregular wounds, induce skin tissue remodeling, promote blood vessel repair and hair follicle regeneration, and accelerate wound healing.